PELATIHAN LARI-LOMPAT DI PASIR MENINGKATKAN JARAK CAPAIAN LOMPAT JAUH LEBIH PANJANG DARIPADA LARI RINTANGAN PADA SISWA SMPN-11 DENPASAR - Sugianta, I Wayan; Pangkahila, J. Alex; Adiputra, N. (Sport and Fitness Journal; Volume 2, No.2, 2014, 2014)
Success in the long jump is strongly influenced by the explosive power of the leg muscles. Increasing this explosive power will increase the distance long jump performance. In this study conducted with two types of training that is run on the track in the sand and obstacles run, each of which performed a total of five sets and four reps. Training is done in the field SMP-11 Denpasar for six weeks with a frequency of three times in a week. Samples were selected randomly as many as 20 people and the selected sample was divided into two groups, so that each group of 10 people. Group-1 are given run-jump training on the sand group-2 are given obstacles run training. Paired t test was used to analyze differences in the long jump achievement gap between before and after training in each group and the unpaired t test used to analyze differences in the long jump achievement gap between groups of training. Limit of significance used was 0.05. The mean distance long jump performance on the training run around in the sand before training was 3.86 ± 0.33 meters and after training was 4.38 ± 0.34 meter showed a statistically significant difference, p = 0.000 (p<0.05). The mean distance of achievement results before training on obstacles run training was 3.62 ± 0.37 meters and after training was 3.92 ± 0.37, also showed a significant difference p = 0.000 (p<0.05). Differences long jump distance before training outcomes between the two groups was not significant p = 0.190 (p>0.05), while after training between groups showed a significant difference p = 0.010 (p<0.05). Therefore run-jump training in the sand and obstacles run training can increase the distance of the long jump in student SMP-11 Denpasar, where run jump training in the sand beter than obstacles run training. So expect to teachers and sports trainers to implement the training long jump with run jump in sand five reps and four sets in training.
Keywords: run jump in the sand, obstacles run. long jump distance performance.